Dinamika Peran Orang Tua dalam Membentuk Pemahaman Gender Anak di Kota Makassar - Sadriani, Andi (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the dynamics of parents' roles in shaping children's gender understanding in Makassar City, particularly within the context of the intersection of traditional Bugis-Makassar values and modern urban values. This study employed qualitative methods with a phenomenological approach, involving ten informants, parents of children aged 5–12. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model. Data validity was maintained through triangulation of sources, techniques, and member checking. The findings of this study highlight three main points. First, parents' roles in childcare are still heavily influenced by traditional role divisions, with mothers being more dominant in the domestic sphere and fathers in the public sphere. This pattern shapes gender symbols that children internalize from an early age. Second, family parenting is in a phase of negotiation between traditional and modern values. Young families tend to adopt egalitarian patterns, but pressures from tradition and the extended family maintain the strength of traditional values. Third, children respond differently to gender messages. Some adhere to family values, while others question gender boundaries due to exposure to digital media and more egalitarian school environments. These findings reinforce Mead's Symbolic Interactionism perspective, which states that children's gender identity is formed through the process of interpreting symbols from their parents' behavior and their social environment. Overall, this study concludes that children's gender understanding is the result of a dynamic interaction between parenting styles, local culture, and the influence of modernity. Therefore, gender education in families needs to be directed toward a more equal, reflective, and responsive pattern to social development.